A new genus of the family Plagusiidae Dana, 1851, close to Plagusia Latreille, 1804 (Crustacea, Decapoda, Brachyura) - Guinot, Daniole (Zootaxa, 2007)
The new genus Davusia n.gen. is established for Plagusia glabra Dana, 1852, from Australia, a species clearly different from the other known species of Plagusia. The new genus is related to Plagusia Dana, 1851 but is readily distinguished from its described species by differences in the morphology of the front, external maxillipeds, thoracic sternum, and the male abdomen. D. glabra (Dana, 1852) n.comb. is characterized by smooth and practically naked body and pereopods